Upaya Meningkatkan Agility Menggunakan Metode Plyometric Kombinasi Pada Siswa Ekstrakurikuler Basket SD Islam Al Azhar 52 Sidoarjo - Tatang Rizky Junaidi; Noortje Anita Kumaat; Achmad Widodo; Panji Bana (MAN Insan Cendekia Jambi, 2025)
This study aimed to improve the agility of extracurricular students using a combination of plyometric exercises, where several plyometric exercises were combined into one drill. These plyometric exercises consisted of single leg hops, lateral jumps, tuck jumps, and squat jumps. The participants in this study were 15 extracurricular basketball students from SD Islam Al- Azhar 52 Sidoarjo, consisting of 6 males and 9 females. The students will undergo combined plyometric training for 6 weeks, divided into 2 cycles, with each cycle lasting 3 weeks. Before and after each cycle, an assessment was conducted using the Z Sprint Test. The study results showed a significant improvement in the plyometric exercise intervention. In the first cycle, the improvement was not yet sufficient, with the average score increasing from 6.14 to 6.08 (standard deviation 6.5, percentage increase: 0.98%, and p-value = 0.003). In the second cycle, a significant improvement in students' agility development began to be observed, from a score of 6.08 to 5.37 (standard deviation 30.6, percentage increase 11.68%, and P- value < 0.001). The overall results of the intervention process showed an impressive improvement from 6.14 to 5.37 (standard deviation 30.5, percentage increase 12.54%, and p- value < 0.001). Other factors, particularly facilities, also contributed to the significant improvement in the second cycle. In essence, plyometric intervention over 6–10 weeks has been proven to enhance athletes' agility, particularly among younger individuals.